STUDENTS’ ABILITY IN TRANSFORMING A SENTENCE: DEEP AND SURFACE STRUCTURE - Afrida, Nina; Khairurrahmi (JL3T (Journal of Linguistics, Literature and Language Teaching), 2016)
The present study aims at exploring students’ difficulties in determining deep and surface structure in sentences. The study used quantitative descriptive as a research design. Test and questionnaire were employed as data collection technique. The population of the study is all seventh semester students of English Education Department, since they have studied syntax in the previous semesters. 50 students were sampled in this study. The study reveals that most of students cannot transform deep structure into surface structure. They only can identify the surface structure of simple sentences. The study also shows that English Education Department students find much difficulty in determining the labeling of the words in surface structure, for they cannot classify the class of wordos in surface structure. The study suggests that the ability to differentiate word categories be essential in transforming the surface structure generated through deep structure.